Comparative evaluation of starches obtained from dioscore species as intragranular tablet disintegrant (2008)
Starches from four Dioscorea species namely Dioscorea dumetorum (bitter yam), D. oppositifolia (Chinese yam), D. alata (water yam) and D. rotundata (white yam) have been evaluated as disintegrants in chloroquine phosphate tablet formulations in comparison with official corn starch. The mechanical and drug release properties of the tablets were assessed. The results showed that the ranking of the effectiveness of the starches as intragranular disintegrant was water > white > corn > Chinese> bitter. The disintegrant concentration had significant (p < 0.001) effects on the disintegrant efficiency. The four experimental starches compared favorably and in some cases showed better efficiency as intragranular disintegrant than corn starch and could be further developed for use in commercial tablet formulation.